An Analysis of Money Demand and Inflation in the Islamic Republic of Iran - Goswami, Mangal (IMF Working Papers; Working Paper ;, 2002)
This study examines money demand and inflation dynamics in the Islamic Republic of Iran using quarterly data for the period 1990/91-2001/02 and tests whether the disinflation during 2000/01-2001/02 represents a structural break in the data. A long-run money market equilibrium condition is identified and the short-run behavior of the inflation, measured in terms of non-administered component of the consumer price index (CPI) is modeled conditional on the disequilibria in the money market. Estimation results indicate that the stabilization of the exchange rate on account of strong oil revenues during 2000/01-2001/02 buoyed the demand for domestic money and contributed to the decline in inflation. Tests of model stability do not point to a structural shift in the inflation equation during the period of analysis.